2015
DOI: 10.1523/jneurosci.1099-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Signaling Mediates Hair Cell Regeneration by Repressingp27kip andsox2in Supporting Cells

Abstract: During development, otic sensory progenitors give rise to hair cells and supporting cells. In mammalian adults, differentiated and quiescent sensory cells are unable to generate new hair cells when these are lost due to various insults, leading to irreversible hearing loss. Retinoic acid (RA) has strong regenerative capacity in several organs, but its role in hair cell regeneration is unknown. Here, we use genetic and pharmacological inhibition to show that the RA pathway is required for hair cell regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 83 publications
(10 reference statements)
0
21
0
Order By: Relevance
“…Thus, RA has a pro-proliferative function. RA is also required for support cell proliferation and HC regeneration in the zebrafish ear and lateral line [58 ]. Ectopic expression of a dominant negative RA receptor (dnRAR) blocks regeneration by preventing support cell proliferation, possibly by maintaining expression of the cell cycle inhibitor cdkn1bb ( p27 kip ) [58 ], which is normally downregulated immediately after neuromast HC ablation [27 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, RA has a pro-proliferative function. RA is also required for support cell proliferation and HC regeneration in the zebrafish ear and lateral line [58 ]. Ectopic expression of a dominant negative RA receptor (dnRAR) blocks regeneration by preventing support cell proliferation, possibly by maintaining expression of the cell cycle inhibitor cdkn1bb ( p27 kip ) [58 ], which is normally downregulated immediately after neuromast HC ablation [27 ].…”
mentioning
confidence: 99%
“…RA is also required for support cell proliferation and HC regeneration in the zebrafish ear and lateral line [58 ]. Ectopic expression of a dominant negative RA receptor (dnRAR) blocks regeneration by preventing support cell proliferation, possibly by maintaining expression of the cell cycle inhibitor cdkn1bb ( p27 kip ) [58 ], which is normally downregulated immediately after neuromast HC ablation [27 ]. Intriguingly, Notch downregulation also reduces cdkn1bb [16 ], suggesting that the downregulation of Notch and the activation of RA signaling may act together or in parallel to regulate cell proliferation during regeneration (Figure 2e).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The RA pathway is activated immediately after the loss of hair cells, accelerating the proliferation of cell precursors, and regulating the expression of two key genes, P27kip and SOX2. The results have indicated that RA can be used as an essential signal for the regeneration of hair cells 34 . In the cochlea of rats fed with all-trans retinoic acid (ATRA), the protection of the organ of corti is more likely to occur than in the cochlea of those feds with oil and saline.…”
Section: Discussionmentioning
confidence: 96%
“…RA has the additional capacity to be reproduced in several organs, but its role in the reproduction of HCs has not been fully recognized. This signaling pathway is likely to be a promising method for hearing restoration [60].…”
Section: Retinoic Acidmentioning
confidence: 99%